Applying GIS-assisted modelling to predict soil erosion for a small agricultural watershed within sloping lands in Northern Vietnam - Phai, Do Duy; Orange, Didier; Migraine, J. B.; Tran Duc Toan; Vinh, N.C. (2007)
GIS-assisted distributed modelling is particularly useful for supplying information to decision-makers regarding land-use, water management and environmental protection. This study deals with the prediction of soil losses by a simple distributed and GIS-assisted model within a small experimental agricultural watershed on sloping lands in northern Vietnam (<1 km2). The Predict and Localise Erosion and Runoff (PLER) model predicts the spatial and temporal distribution of soil erosion rates; thus it can be used to identify erosion hot spots in a watershed. The model has been built specifically to take into account steep slopes. It is a conceptual erosion model on a physical base. Indeed, the model imitates soil erosion as a dynamic process which includes three phases: i) detachment, ii) transport and iii) deposition. In this study the PLER model was used for two complete years, 2003 and 2004. The disparity for the soil erosion quantity between the experiment and the run model was 5.1% in 2003 and 4.9% in 2004, even though these two years had a very different annual amount of rain. Indeed, 40% of the rainfall events were of a strong intensity (>75 mm hr-1) in 2003 as apposed to only 4% in 2004. The amount of rainfall in 2003 and 2004 was 1,583 mm and 1,353 mm, respectively. The PLER model took into account this discrepancy in the rainfall characteristics between the two years. Between April to September, the disparity fluctuates between just 4.7%-5.3%. The maps drawn by the PLER model underline that the erosion process occurs mainly at the top of the landscape and highlights a different behaviour for detachability and soil erosion between the western and the eastern parts of the studied watershed.